(untitled) (Herald of Journalism, 2019)
The article assesses the contribution of the Alash intelligentsia to the development of the native language. An attempt to officially speak in the Kazakh language in the government of Alashorda is confirmed by the actual data. It is said about the importance of textbooks of Alash leaders, which they wrote for teaching at school in their native language. In addition, the author analyzes the articles of Alash figures about the Kazakh language. The purpose of this paper is to estimate the linguistic position of the government of Alashorda, party Alash, showing the beneficial use of their activities, which became an example for us. The idea of scientific research is to explain the purpose and essence of the struggle for language, reminding today’s generation that the “Kazakh” language on Earth was eternal. The article shows that the tip of the Soviet ideology was directed against the idea of “Eternal Elya”. The article has scientific and practical significance. Learning from the past, you need to be able to predict the future. The law of the Republic of Kazakhstan “On language” is the guide and the norm of legal responsibility of each citizen of the Republic of Kazakhstan. The research, transmitted in the process of writing articles, can be used to teach the history of the domestic journalism.